2019
DOI: 10.1016/j.ultrasmedbio.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Increased Vascular Signal in Arthritis-Prone Rats Without Joint Swelling Using Superb Microvascular Imaging Ultrasonography

Abstract: This study aimed to determine whether ultrasonography (US) can detect increased vascular signal in the synovial tissue prior to overt synovitis in rheumatoid arthritis (RA). Env-pX rats that spontaneously develop RA-like synovitis were used. Ankle joints of 15 pre-morbid env-pX rats were observed with power Doppler and superb microvascular imaging (SMI) using an ultrahighfrequency (8-24 MHz) probe. Signal values were counted as the number of pixels. The total number of vessels and vessel area in the synovial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Overall, 19 original studies of SMI application in rheumatology were found and 18 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] of them were analysed because we were not able to obtain the full text of one publication. The majority of the included studies were conducted in Japan [ 11 , 12 , 13 , 14 , 15 ], China [ 16 , 17 , 18 , 19 , 20 ], and Turkey [ 21 , 22 , 23 , 24 ]; single studies were conducted in Australia [ 25 ], Italy [ 26 ], South Korea [ 27 ] and the United Kingdom [ 28 ]. Reference screening provided three additional papers, but only one fulfilled the inclusion criteria and was included for analysis [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 19 original studies of SMI application in rheumatology were found and 18 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] of them were analysed because we were not able to obtain the full text of one publication. The majority of the included studies were conducted in Japan [ 11 , 12 , 13 , 14 , 15 ], China [ 16 , 17 , 18 , 19 , 20 ], and Turkey [ 21 , 22 , 23 , 24 ]; single studies were conducted in Australia [ 25 ], Italy [ 26 ], South Korea [ 27 ] and the United Kingdom [ 28 ]. Reference screening provided three additional papers, but only one fulfilled the inclusion criteria and was included for analysis [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Supplemental Table S1 depicts the baseline characteristics of the identified studies and enrolled patients. The most studied rheumatic disease was RA (52.63% of studies) [ 11 , 12 , 13 , 14 , 16 , 18 , 19 , 20 , 26 ] representing up to 63.15% of the studies when analysed in a mixed sample together with non-RA arthritis [ 15 , 28 ]. The main target of the research was synovial vascularity of the joints (84.21%).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that SMI played an important role on evaluation of RA activity, especially in subclinical synovitis than in clinical. 15,16 However, there were few studies on the application of SMI in PVNS. In our study, SMI can indeed improve the detection rate of synovial blood flow and the grade of synovial blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with CDFI, SMI can improve the detection rate of synovial blood flow and the grade of synovial blood flow. Studies have shown that SMI played an important role on evaluation of RA activity, especially in subclinical synovitis than in clinical 15,16 . However, there were few studies on the application of SMI in PVNS.…”
Section: Discussionmentioning
confidence: 99%
“…To monitor the progression of synovitis chronologically, joint US was used in this study. Up to now, there are few studies that use US to evaluate arthritis in small animals (Clavel et al, 2008;Horie et al, 2019;Liao et al, 2016). The recent development of US makes it possible to image more clearly using higher frequencies without motion artifacts.…”
Section: Discussionmentioning
confidence: 99%